Principal Components as a Measure of Live Weight and Morphometric correlates in Pre- Pubertal Hetero (2016)
An experiment was conducted to elucidate the interdependence of conformation traits and to predict body weight from their independent factor scores using principal component extraction method. Bodyweight and eight morphometric variables namely body length, chest girth, thigh circumference, thigh length, hind leg length, fore leg length, ear length, and head length of 47 pre pubertal heterogeneous rabbit crosses were measured. Mean body weight were 993.31±40.66 and 1110.50±63.61 for male and female rabbits, respectively. Phenotypic variations between body weight and other morphometric variables were highly significant (r = 0.37 – 0.86 at P<0.01). Pairwise correlations ranged from moderate to high for most of the measured variables. However, there were no significant correlations between head length and ear length; fore leg length and ear length; thigh circumference and ear length. Cumulative contribution ratio from the first principal component (PC1) to the fourth principal component (PC4) was 85.50%. The PC1 accounted for 34.98% of the total variance with loadings for body length, chest girth, thigh circumference, hind leg length and fore leg length and described the general size. PC2 was determined by thigh length and accounted for 22.15% of the total variance, while PC3 had loading for head length and accounted for 14.77% of the generalized variance. The PC4 loaded for ear length, accounting for 13.60% of the generalized variance. The stepwise regression for orthogonal variables derived from factor scores accounted for about 84% of the variation observed in body weight of rabbits whereas the original morphometric variables accounted for 89.7% of the observed variation in body weight.